2017
DOI: 10.18267/j.cebr.180
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Student Entrepreneurship in Visegrad Four Countries: Guesss Evidence

Abstract: The aim of our paper is to find out what drives student entrepreneurs in Visegrad (V4) countries (i.e. the Czech Republic, Hungary, Poland, Slovakia) in their business activities. Our analysis is built on 2016 data from GUESSS project -an extensive academic study on student entrepreneurship, and our main sample comprises of 15,971 V4 university students. Potential drivers from individual human and social capital characteristics, perceived institutional support, and demographic attributes are examined, using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Scholars are striving to understand more why an individual has an intention and decision to become an entrepreneur (Burger & Blažková, 2020;Dvouletý, 2017;Holienka et al, 2017;Krueger et al, 2000;Liñán & Chen, 2009). However, researches on academic entrepreneurship or invention commercialisation, especially in exploring the role of contextual factors in shaping intention to commercialise invention among scientists, are rather sparse (Nguyen et al, 2018;Perkmann et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Scholars are striving to understand more why an individual has an intention and decision to become an entrepreneur (Burger & Blažková, 2020;Dvouletý, 2017;Holienka et al, 2017;Krueger et al, 2000;Liñán & Chen, 2009). However, researches on academic entrepreneurship or invention commercialisation, especially in exploring the role of contextual factors in shaping intention to commercialise invention among scientists, are rather sparse (Nguyen et al, 2018;Perkmann et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Another argument in the discussion of this point is that some important factors on the entrepreneurial propensity such as the opportunity recognition, self-confidence, fear of failure, role model, self-efficacy and internal locus of control, have less impact on women; because women tend to be more sensitive than men to a variety of non-monetary incentives, and for women the choice to be an entrepreneur is often linked to necessity and not for opportunity (Minniti and Nardone, 2007). Finally, having an entrepreneurial father or mother is a positive influence on entrepreneurial intention of their offspring; at the time, this influence could also generate the opposite effect or negative, and lead the offspring to have no entrepreneurial intention and therefore not identify with their father or mother (Criaco et al, 2017;Holienka et al, 2017). This argument also helps explain in part the fact that some women or men identify less or more with their parents, father or mother, or even not fully identify for certain things with them or some of them.…”
Section: Discussionmentioning
confidence: 99%
“…The financial crisis of 2008 has harshly influenced the regional labour market, and the issue of employment has become progressively momentous since then (Gubik and Farkas, 2019). The youth sector has inhibited significant effort and involvement in entrepreneurial projects (Szerb and Imreh, 2007; Holienka et al , 2017; Dallago, 2017; Petrová, 2019; Gubik and Farkas, 2019; Hartšenko and Küttim, 2019) and became the driving force of the rapidly expanding Visegrád Four entrepreneurship and start-up ecosystems (Andrejczuk and Jałukowicz, 2015). Pilkova et al (2017) found that personality traits and personal-related factors are one of the main drivers for the entrepreneurial intentions among youth in Visegrád countries to pursue their entrepreneurial goals.…”
Section: Introductionmentioning
confidence: 99%